2022
DOI: 10.1186/s12984-022-00999-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial magnetic stimulation in modulating cortical excitability in patients with stroke: a systematic review and meta-analysis

Abstract: Background Transcranial magnetic stimulation (TMS) has attracted plenty of attention as it has been proved to be effective in facilitating motor recovery in patients with stroke. The aim of this study was to systematically review the effects of repetitive TMS (rTMS) and theta burst stimulation (TBS) protocols in modulating cortical excitability after stroke. Methods A literature search was carried out using PubMed, Medline, EMBASE, CINAHL, and PEDr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 94 publications
(197 reference statements)
2
39
0
Order By: Relevance
“…The previous studies showed that rTMS could modulate cortical excitability (75,76), and our study confirmed this again. Similar to our results, a recent meta-analysis performed by Bai et al (77) found that HF-rTMS enhanced the cortical excitability of the affected M1 and iTBS, which also showed superior effects in rebalancing bilateral excitability. However, we found no significant inhibitory effect of HF-rTMS on contralateral M1.…”
Section: Discussionsupporting
confidence: 92%
“…The previous studies showed that rTMS could modulate cortical excitability (75,76), and our study confirmed this again. Similar to our results, a recent meta-analysis performed by Bai et al (77) found that HF-rTMS enhanced the cortical excitability of the affected M1 and iTBS, which also showed superior effects in rebalancing bilateral excitability. However, we found no significant inhibitory effect of HF-rTMS on contralateral M1.…”
Section: Discussionsupporting
confidence: 92%
“…A recent meta-analysis revealed that the high-frequency rTMS over the ipsilesional M1 enhanced its excitability without affecting that of the contralesional M1. On the other hand, the low-frequency rTMS protocol not only decreased the contralesional M1 excitability but also enhanced that of the ipsilesional M1, further supporting the bimodal balance recovery model ( Bai et al, 2022 ).…”
Section: Motor Rehabilitationsupporting
confidence: 59%
“…However, in the convalescent phase group, ≥10 Hz rTMS was the best protocol which was superior to ITBS. Previous studies ( 39 , 40 ) indicated that HF-rTMS enhanced only the cortical excitability of the affected M1. In contrast, ITBS could modulate interhemispheric imbalance by increasing the cortical excitability of the affected M1 and suppressing that of the unaffected M1.…”
Section: Discussionmentioning
confidence: 90%